1989
DOI: 10.1016/0014-5793(89)81020-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification by flow cytometry of two distinct rhodamine‐123‐stained mitochondrial populations in rat liver

Abstract: Isolated rat liver mitochondria were split into three fractions of increasing density when applied to a Percoll gradient. NADH-ubiquinone oxidoreductase, succinate dehydrogenase and cytochrome-c oxidase but not F,-ATPase activities increased with density as well as respiratory rate in state 3 and the respiratory control index. Flow cytometry of mitochondrial density fractions stained with rhodaminerevealed the occurrence in each density fraction of two distinct mitochondrial populations with different fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 22 publications
1
37
1
Order By: Relevance
“…Under the same circumstances, the percentages of mitochondria fluorescence populations changed markedly during the first hour of extrauterine life (Table 2). Thus, the percentage of the HFP sharply decreased while that of the LFP increased ( Table 2), suggesting that the HFP is an immature form of mitochondria that is converted into the mature one, the LFP [7,8], which is the major mitochondrial form in the adult rat liver [6]. In addition, the postnatal increase in the LPF/HFP ratio observed in our experiments (Table 2) may be related to the postnatal improvement in mitochondrial function (Table 1) Pollak et al [1,17] postulated that the acquisition of energy-transducing mitochondria after birth would be mediated by mitochondrial enrichment in ATP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the same circumstances, the percentages of mitochondria fluorescence populations changed markedly during the first hour of extrauterine life (Table 2). Thus, the percentage of the HFP sharply decreased while that of the LFP increased ( Table 2), suggesting that the HFP is an immature form of mitochondria that is converted into the mature one, the LFP [7,8], which is the major mitochondrial form in the adult rat liver [6]. In addition, the postnatal increase in the LPF/HFP ratio observed in our experiments (Table 2) may be related to the postnatal improvement in mitochondrial function (Table 1) Pollak et al [1,17] postulated that the acquisition of energy-transducing mitochondria after birth would be mediated by mitochondrial enrichment in ATP.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the conversion of the HFP into the LFP depends on the synthesis of mitochondrial proteins coded either by nuclear or by mitochondrial DNA. Since the changes in LFP/HFP ratio are probably associated with rh-123 binding to the F,F,-ATPase complex [6,7,11,13], it may be suggested that proteins involved in LFP-HFP interconversion are subunits of this enzyme. This is in agreement with our previous suggestion that the HFP is transformed into the LFP by the incorporation of some components of F,F,-ATPase, resulting in an increase in mitochondrial efficiency [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, R 123 binds also to sites freely accessible in deenergized mitochondria (60). Therefore, these sites may contribute to the fluorescence structure arising from the oxidation of DHR to R 123.…”
Section: Discussionmentioning
confidence: 99%